Mediating Impact of Occupational Stress on Leadership Styles and Job Performance in Asset Maintenance-Transmission Division, Tenaga Nasional Berhad - S.B. Thilakavathi, Balakrishnan (2012)
Tenaga Nasional Berhad (TNB) is a monopoly company being in charge of power utility. TNB as a whole strives to cater power electricity to all consumers situated in Malaysia and Sabah with the aid of its core division which includes Asset Maintenance, Transmission. TNB focuses on how to “keep the lights on” without interruption. Such demanding situations and requirements at times lead to stress to employees regardless of their position and status in the organization. The problem of the occupational stress may affect the performance of the TNB’s employees. Therefore, leaders are identified to execute important roles and task to serve, to deliver and to excel in the business. A study was performed to find out the best leadership style that TNB should implement in her organization. Using a proportionate stratified random sampling, questionnaire survey was employed and distributed to the employees of Asset Maintenance, Transmission Division via their General Manager (Human Resource Management & Administration Services), Transmission Division, TNB. A total of 175 employees participated in this study, representing a response rate of 55.21%. However the actual usable data was 53.94% (171). Hierarchical multiple regression analyses were conducted to test the hypotheses posited in this study. The regression results indicated that: (1) it is partially supported for a significant relationship between leadership style and job performance, (2) it is partially supported for a significant relationship between leadership style and occupational stress. The findings showed that preferable leadership style was democratic, in which potent to be predictors of job performance within the Asset Maintenance Department of Transmission Division in TNB.